Whatever Happened to the Mother? A New Look at the Old Problem of the Mother's Brother in Three New Guinea Societies: Gimi, Daribi, and Iatmul. - Gillison, Gillian (Oceania, 2016)
Kinship systems cannot be analysed as straightforward translations of the 'facts of nature' when those facts are limited to the production of a child by a heterosexual couple. Based upon analyses of three New Guinea societies ( Gimi, Daribi, and Iatmul), I suggest that kinship systems take account - often by denying - certain 'facts' of human reproduction when those facts are extended beyond coitus and parturition to include both the very long period of infantile dependence upon one significant caregiver (always the mother in the societies in question and nearly universally) and the subsequent requirement for the child to be extracted from a dyadic maternal universe. Separation from mother is as critical to the survival and development of the individual as is the original prolonged and intense attachment to her. The question, then, is not whether indigenous peoples accurately understand coitus and conception - they do - but rather the ways in which they manipulate that knowledge in rules and rites of kinship in order to manage the growth and development of a child long after parturition. Rules of kinship and social relations neither ignore nor exist apart from theories of procreation as many anthropologists now claim. Rather, it is precisely because theories of procreation indicate and idealise the flow of bodily substance during coitus and pregnancy that they serve as organisational premises for social relations. The fact that kinship is a symbolic construction does not mean that it is wholly ideological nor, like a language, free to vary in ways that are arbitrary and unconnected to the 'facts of life' as Westerners understand them. Even when interlocutors openly deny such understanding and knowledge, especially of the male role in coitus and conception, evidence to the contrary is abundantly provided in myth, ritual, and indigenous theories of procreation. What kinship systems often do show, however, is a strategic denial of the role of the mother who, upon deeper understanding of indigenous concepts of procreation, turns out to be a 'sterile vessel' or without substantial contribution to her child. I illustrate this premise by extending earlier analyses of Gimi kinship and reexamining certain materials on neighbouring Daribi provided by Roy Wagner and on Iatmul peoples of the Sepik River as originally described in Naven by Gregory Bateson eighty years ago.